1154. Safety, Tolerability, and Viral Pharmacodynamics of the IgG Monoclonal Antibody Sotrovimab Administered via Intramuscular Injection for the Treatment of Early Mild-to-Moderate COVID-19. (15th December 2022) - Gupta, Anil K; Perez-Rodríguez, Maria Teresa; Gonzalez-Rojas, Yaneicy; Ramgopal, Moti; Free, Almena; Han, Jennifer; Moore, Jennifer; Banerjee, Rudrani; Yates, Phillip; Walker, Jill; Schnell, Gretja; Connolly, Mary Beth; et al.
Abstract: Background: There is a continued need for therapeutics for the treatment of COVID-19, including intramuscular (IM) agents, which will enable broader use across a variety of healthcare delivery settings. Methods: COMET-PEAK (NCT04779879) is a 3-part study evaluating the safety, tolerability, pharmacokinetics (Part A), and viral pharmacodynamics (PD) of sotrovimab as treatment in adults ≥ 18 years with early mild/moderate COVID-19. In Parts B and C, the safety, tolerability and viral PD of sotrovimab administered as a 500 mg intravenous (IV) infusion or as a 500 mg or 250 mg IM injection, respectively, was evaluated. The primary objective for Parts B and C was to compare the virologic response of sotrovimab IM to IV, with an endpoint of mean area under the curve (AUC) of SARS-CoV-2 viral load as measured by qRT-PCR from Day 1 to Day 8 (AUCD1-8 ) in nasopharyngeal swabs and predefined 90% confidence interval (CI) limits of 0.5-2.0 indicating equivalence. Results: A total of 167 and 157 participants were enrolled in Part B and C, respectively, from February-July 2021. The median age of participants was 47 and 42 years in Part B and C, respectively, and ∼50% had ≥ 1 risk factor for progression to severe disease. The viral load at baseline and through Day 29 of follow-up for each arm is shown in Table 1 and Figure 1. The primary objective was met for both study parts: the ratio of the least square geometric mean viral load AUC(D1-8) of sotrovimab IM vs IV was 1.04 (90% CI, 0.98, 1.09) and 1.02 (90% CI, 0.94, 1.11), for Part B and C, respectively. Through Day 29 of follow-up, the most common adverse event was injection site reactions (ISRs) in the IM arms. A total of 10 (12%) participants in the 500 mg IM group and 4 (5%) participants in the 250 mg IM group experienced an ISR, all Grade 1. Serious adverse events were uncommon, and related to COVID-19 progression, including one death in the 250 mg IM arm (Table 2). ISRs aside, there were few treatment-related AEs (2/84 IV, 1/82 IM) in Part B, none serious. Conclusion: IM administration of sotrovimab 500 mg and 250 mg each demonstrated equivalence to 500 mg sotrovimab IV in viral load assessments. Overall, there were no treatment-related serious AEs and sotrovimab was well tolerated. An 500 mg IM formulation will allow for expanded treatment potential with sotrovimab. Funding: Vir/GSK (NCT04779879). Disclosures: Anil K. Gupta, MD, Vir Biotechnology: Advisor/Consultant|Vir Biotechnology: Grant/Research Support|Vir Biotechnology: Speaker Moti Ramgopal, MD, FACP, FIDSA, AbbVie: Grant/Research Support|Gilead Sciences Inc.: Advisor/Consultant|Gilead Sciences Inc.: Grant/Research Support|Gilead Sciences Inc.: Honoraria|Gilead Sciences Inc.: Stocks/Bonds|GlaxoSmithKline: Advisor/Consultant|GlaxoSmithKline: Grant/Research Support|GlaxoSmithKline: Honoraria|GlaxoSmithKline: Stocks/Bonds|Janssen Research & Development LLC: Advisor/Consultant|Janssen Research & Development LLC: Grant/Research Support|Janssen Research & Development LLC: Honoraria|Janssen Research & Development LLC: Stocks/Bonds|Merck: Advisor/Consultant|Merck: Grant/Research Support|Merck: Honoraria|Merck: Stocks/Bonds|Shionogi: Grant/Research Support|ViiV: Advisor/Consultant|ViiV: Grant/Research Support Jennifer Han, MD, GlaxoSmithKline: Employee Jennifer Moore, MD, GlaxoSmithKline: Employee Rudrani Banerjee, PhD, GSK: Employee|GSK: Stocks/Bonds Phillip Yates, PhD, GSK: Employee during conduct of this research|GSK: Stocks/Bonds Jill Walker, PhD, GlaxoSmithKline: Employee Gretja Schnell, PhD, Vir Biotechnology: Employee|Vir Biotechnology: Stocks/Bonds Mary Beth Connolly, PharmD, GSK: Employee|GSK: Stocks/Bonds Andrea L. Cathcart, PhD, Vir Biotechnology: Employee|Vir Biotechnology: Stocks/Bonds Varsha Imber, MSc, GSK: Employee|GSK: Stocks/Bonds Rabia Anselm, n/a, GSK: Employee|GSK: Stocks/Bonds Lindsay Winograd, MSc, GSK: Employee|GSK: Stocks/Bonds Nancy Haeusser, n/a, GSK: Employee|GSK: Stocks/Bonds Scott Segal, MD, GSK: Employee|GSK: Stocks/Bonds Andrew Skingsley, MD, GlaxoSmithKline: Employee|GlaxoSmithKline: Stocks/Bonds Melissa Aldinger, PharmD, Vir Biotechnology: Employee|Vir Biotechnology: Stocks/Bonds Amanda Peppercorn, MD, GlaxoSmithKline: Employee|GlaxoSmithKline: Stocks/Bonds.